Comparative evaluation of fracture resistance and push-out bond strength of glass fiber post with composite core and single-unit post and core system luted with two different resin cements: An in vitro study - Ishika Garg; Pragya Kumar; Sonali Taneja (Wolters Kluwer Medknow Publications, 2024)
Aim: The aim of the study was to compare the fracture resistance and push-out bond strength of glass fiber post (GFP) with composite core and single unit post and core system luted with two different resin cements. Methods: Sixty-four mandibular premolars were chosen as the sample for the study. Sample preparation was done, and specimens were randomly divided into two groups (n = 32) each according to the type of post used: Group I - RelyX GFP, Group II - Edelweiss post and core. They were further subdivided in two subgroups based on luting cements: subgroup A: RelyX U200 Adhesive Resin cement and subgroup B: SoloCem resin cement. Fracture resistance was measured in half of the prepared specimens by subjecting a load of 1 mm/min. The load was subjected along the long axis of the tooth at an angle of 45° until failure occurred using the universal testing machine. Half of the samples were divided into three horizontal thirds, i.e., coronal, middle, and apical, and push-out bond strength was evaluated at a rate of 0.5 mm/min. The scores were subjected to statistical analysis using independent t-test and SPSS Version 22.0. Results: Group I showed nonsignificantly better fracture resistance than Group II irrespective of type of luting agent used. Subgroup B showed nonsignificantly higher fracture resistance than subgroup A irrespective of the post used. Subgroup B was nonsignificant better push-out bond strength than Subgroup A (P < 0.05). Push-out bond strength of Group II was significantly better than Group I irrespective of the luting agent. Conclusion: Fiber post showed nonsignificantly better fracture resistance than Edelweiss post and core system. SoloCem showed nonsignificantly better fracture resistance and push-out bond strength with Edelweiss than RelyX U200.